Developing a telehealth readiness assessment framework and tool for least developed countries: A case of yemen - Al-Fadhli A.A.; Othman M.; Al-Rejal H.M.A.; Al-Jamrh B.A. (Institute of Medico-Legal Publications, 2023)
adoption; article; developed country; health care organization; human; interview; medical information; public health; rural area; telehealth; Yemen